Colorectal MALT lymphoma: a rare clinical entity - Fischbach, Wolfgang (Zeitschrift für Gastroenterologie, 2018)
Background Data on colorectal lymphoma in general and on MALT (mucosa-associated-lymphoid tissue) lymphoma, in particular are, very rare. There are no existing recommendations from current guidelines for how to manage these patients. We here report our experience from a clinical series.Aim The aim of this study is to present clinical features and the endoscopic appearance of colorectal MALT lymphoma and therapeutic approaches.Methods Seven patients (5 male and 2 female, aged 47 – 75 years) were diagnosed to have colorectal MALT lymphoma. All patients underwent a full staging work-up. A concurrent gastric MALT lymphoma was present in 2 patients. Follow-up was 37 (0 – 53) months.Results Colorectal MALT lymphoma was diagnosed by screening or staging colonoscopy in 3 and 1 patient, revealing no clinical symptoms, respectively. Two patients complained about fatigue, obstipation, and a change in bowel habits. The endoscopic appearance of the MALT lymphoma comprised obstructive tumors (n = 2), polyps (n = 3), a flat lesion (n = 1), and vascular angiectasia (n = 1). In 6 cases, colorectal MALT lymphoma presented as a solitary lesion. Following endoscopic polypectomy, surgical resection, Helicobacter pylori eradication therapy, or systemic immune-chemotherapy, complete remission of lymphoma was achieved in 5 cases, while the outcome is unknown or cannot yet be estimated in 2 cases.Conclusion A treatment and management approach based on the clinical and local presentation of the lymphoma and its involvement is proposed.
Keywords: colorectal MALT lymphoma; clinical presentation; endoscopic appearance; therapy; management